BRAF mutation analysis in circulating free tumor DNA of melanoma patients treated with BRAF inhibitors. Issue 6 (December 2015) - Gonzalez-Cao, Maria; Mayo-de-las-Casas, Clara; Molina-Vila, Miguel A.; De Mattos-Arruda, Leticia; Muñoz-Couselo, Eva; Manzano, Jose L.; Cortes, Javier; Berros, Jose P.; Drozdowskyj, Ana; Sanmamed, Miguel; Gonzalez, Alvaro; Alvarez, Carlos; et al.
Abstract : BRAFV600E is a unique molecular marker for metastatic melanoma, being the most frequent somatic point mutation in this malignancy. Detection of BRAFV600E in blood could have prognostic and predictive value and could be useful for monitoring response to BRAF-targeted therapy. We developed a rapid, sensitive method for the detection and quantification of BRAFV600E in circulating free DNA (cfDNA) isolated from plasma and serum on the basis of a quantitative 5′-nuclease PCR (Taqman) in the presence of a peptide−nucleic acid. We validated the assay in 92 lung, colon, and melanoma archival serum and plasma samples with paired tumor tissue (40 wild-type and 52 BRAFV600E). The correlation of cfDNA BRAFV600E with clinical parameters was further explored in 22 metastatic melanoma patients treated with BRAF inhibitors. Our assay could detect and quantify BRAFV600E in mixed samples with as little as 0.005% mutant DNA (copy number ratio 1 : 20 000), with a specificity of 100% and a sensitivity of 57.7% in archival serum and plasma samples. In 22 melanoma patients treated with BRAF inhibitors, the median progression-free survival was 3.6 months for those showing BRAFV600E in pretreatment cfDNA compared with 13.4 months for those in whom the mutation was not detected ( P =0.021). Moreover, the median overall survival for positive versus negative BRAFV600E tests in pretreatment cfDNA differed significantly (7 vs. 21.8 months, P =0.017). This finding indicates that the sensitive detection and accurate quantification of low-abundance BRAFV600E alleles in cfDNA using our assay can be useful for predicting treatment outcome.